Determinants and interactions of sustainability and risk management of commercial cattle farmers in Namibia - Jessica Ingenillem; Joachim Merz; Stefan Baumgärtner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
We study the determinants and interactions of sustainability and risk management with a cross-sectional dataset on commercial cattle farming in semi-arid rangelands in Namibia. Cattle farmers in Namibia act within a coupled ecological-economic system that is subject to extensive degradation and high environmental risk. Based on survey data, we develop variables for sustainability and risk management within this context, identify their determinants and analyse relevant interactions. Our results show that the ecosystem condition is positively influenced when financial risk management strategies are applied. On-farm risk management, like additional feed for cattle or resting part of the rangeland, and collective risk management through interest groups or governmental support, instead, do not impact on the sustainability of the farm. Risk management itself is predominantly influenced by various risks linked to the farming business and the farmers' educational background. Furthermore, the gathered experience through operation time on farm decreases the application of on-farm risk management and favours the use of financial and collective risk management. Additionally, collective risk management is influenced by risk preferences, indicating that farmers who are more risk friendly apply forms of joint risk management strategies to a lesser extent. Risk friendliness is also negatively related to the economic sustainability, specified as the ability to sustain the livelihood of the farmer. However, the results show no indication whatsoever that time preferences impact on either sustainability or risk management.
Keywords: 330; cattle farming; ecological-economic system; financial instruments; precipitation; risk management; semi-arid rangelands; sustainability